Ataxia Oculomotor Apraxia Type 1 in the Siblings of a Family: A Novel Mutation - KARIMZADEH, Parvaneh; KHAYYATZADEH, Simin; ESMAIL NEJAD, Shaghayegh Sadat; HOUSHMAND, Masoud; GHFORANI, MOHAMMAD (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Karimzadeh P, khayatzadeh kakhki S,Esmail Nejad Sh. S., Houshmand M,Ghofrani M. Ataxia oculomotor apraxia 1 in two siblings of a family:a novel mutation. Iran J Child Neurol.Winter 2017; 11(1):78-81. Abstract Although AOA1 (ataxia oculomotor apraxia1) is one of the most common causes of autosomal recessive cerebellar ataxias in Japanese population, it is reported from all over the world. The clinical manifestations are similar to ataxia telangiectasia in which non-neurological manifestations are absent and include almost 10% of autosomal recessive cerebellar ataxias. Dysarthria and gait disorder are the most two common and typical manifestations. Oculomotor apraxia is usually seen a few years after the manifestations start. APTX gene on 9p13.3 chromosome is expressed in the cells of all human body tissues and different mutations had been discovered. Here we report two siblings (a girl and a boy) of consanguineous parents visited at Mofid Pediatrics Hospital in 2015, with history of gait ataxia, titubation, tremor, and oculomotor apraxia around five yr old and after that. The brother showed symptoms of disease earlier and more severe than his sister did. After ruling out the common etiologies of progressive ataxia, we did genetic study for AOA1 that showed a homozygous frameshift mutation as c.418_418 del was found. This mutation was not reported before so this was a new mutation in APTX gene. References 1. Jafar-Nejad P, Maririch SM, Zoghbi HM .The cerebellum and hereditary ataxias. In: Swaiman KF, Ashwal S, Ferriero DM, Schor NF. Swaiman’s Pediatric Neurology Principles, and Practice.15th ed. 2012.P.939-952. 2. Pina-Garza JE. Ataxias. In:Pina-Garza JE. Fenichel Clinical pediatric neurology. 7th ed. 2013.P.215-231. 3. Le Ber I, Moreira MC, Rivaud-Péchoux S, Chamayou C, Ochsner F, Kuntzer T, et al. Cerebellar ataxia with oculomotor apraxia type 1: clinical and genetic studies. Brain 2003; 126:2761-72. 4. Coutinho P, Barbot C. Ataxia with Oculomotor Apraxia Type 1. 2002 Jun 11 [Updated 2015 Mar 19]. In: Pagon RA, Adam MP, Ardinger HH, et al., editors. GeneReviews® [Internet]. Seattle (WA): University of Washington, Seattle; 1993-2016. Available from: https:// www.ncbi.nlm.nih.gov/books/NBK1456/ 5. Shahwan A, Byrd PJ, Taylor AM, Nestor T, Ryan S, King MD. Atypical presentation of ataxia-oculomotor apraxia type 1. Dev Med Child Neurol 2006 Jun; 48(6):529-32. 6. Shimazaki H, Takiyama Y, Sakoe K, Ikeguchi K, Niijima K, et al. Early-onset ataxia with ocular motor apraxia and hypoalbuminemia: the aprataxin gene mutations. Neurology 2002; 59(4):590-5. 7. Yokoseki A, Ishihara T, Koyama A, Shiga A, Yamada M, Suzuki C,and et al. Genotype-phenotype correlations in early onset ataxia with ocular motor apraxia and hypoalbuminaemia. Brain 2011; 134:1387-99. 8. Moreira MC, Barbot C, Tachi N, Kozuka N, Mendonça P, Barros J, Coutinho P, Sequeiros J, Koenig M. Homozygosity mapping of Portuguese and Japanese forms of ataxia-oculomotor apraxia to 9p13, and evidence for genetic heterogeneity. Am J Hum Genet 2001; 68(2):501-8.